Palaeoenvironmental reconstruction of the alluvial landscape of Neolithic Çatalhöyük, central southern Turkey: The implications for early agriculture and responses to environmental change. (November 2017) - Ayala, Gianna; Wainwright, John; Walker, Joanna; Hodara, Rachel; Lloyd, Jerry M.; Leng, Melanie; Doherty, Chris
Abstract: Archaeological discussions of early agriculture have often used the Neolithic village of Çatalhöyük in central southern Turkey as a key example of the restricting effect of environment on agricultural production and organization. Central to these discussions is the palaeoenvironmental reconstruction of the landscape surrounding the site. This paper presents an important new dataset from an intensive coring programme undertaken between 2007 and 2013 in the immediate environs of the site, designed to improve significantly the spatial resolution of palaeoenvironmental data. Using sediment analyses including organic content, magnetic susceptibility, particle size, total carbon and nitrogen contents and carbon isotope analysis, coupled with 3D modelling, we are able to present a new reconstruction of the palaeotopography and sedimentary environments of the site. Our findings have major implications for our understanding of Neolithic agricultural production and social practice. We present four phases of environmental development. Phase 1 consists of the final phases of regression of Palaeolake Konya in the later parts of the Pleistocene, dominated by erosion due to wind and water that created an undulating surface of the marl deposited in the palaeolake. Phase 2 occurs in the latest Pleistocene and early Holocene, and indicates increased wetness, probably characteristic of a humid anabranching channel system, in which there are localized pockets of wetter conditions. In Phase 3a, this infilling continues, producing a flatter surface, and there are fewer pockets being occupied by wetter conditions. The fluvial régime shifts from humid to dryland anabranching conditions. The earliest period of occupation of the Neolithic East Mound coincides with this phase. Phase 3b coincides with the shift of occupation to the West Mound in the Chalcolithic, when there is evidence for a very localized wetter area to the southeast of the West Mound, but otherwise a continuation of the dryland anabranching system. Finally, Phase 4 shows a shift to the pre-modern style of fluvial environment, modified by channelization. This reanalysis demonstrates the importance of extensive spatial sampling as part of geoarchaeological investigations. With this new evidence we demonstrate that the landscape was highly variable in time and space with increasingly dry conditions developing from the early Holocene onwards. In contrast to earlier landscape reconstructions that have presented marshy conditions during the early Holocene that impacted agriculture, we argue that localized areas of the floodplain would have afforded significant opportunities for agriculture closer to the site. In this way, the results have important implications for how we understand agricultural practices in the early Neolithic. Highlights: A four phase palaeoenvironmental reconstruction of the area surrounding Çatalhöyük. Data reveals Neolithic landscape not as wet as previously thought . Results have significant implications for models of early agriculture . Fluvial régime was a dryland anabranching system.